miR-30 Family microRNAs Regulate Myogenic Differentiation and Provide Negative Feedback on the microRNA Pathway - Guess, Martin G. (PLoS One, 2015)
microRNAs (miRNAs) are short non-coding RNAs that can mediate changes in gene expression and are required for the formation of skeletal muscle (myogenesis). With the goal of identifying novel miRNA biomarkers of muscle disease, we profiled miRNA expression using miRNA-seq in the gastrocnemius muscles of dystrophic mdx4cv mice. After identifying a down-regulation of the miR-30 family (miR-30a-5p, -30b, -30c, -30d and -30e) when compared to C57Bl/6 (WT) mice, we found that overexpression of miR-30 family miRNAs promotes differentiation, while inhibition restricts differentiation of myoblasts in vitro. Additionally, miR-30 family miRNAs are coordinately down-regulated during in vivo models of muscle injury (barium chloride injection) and muscle disuse atrophy (hindlimb suspension). Using bioinformatics tools and in vitro studies, we identified and validated Smarcd2, Snai2 and Tnrc6a as miR-30 family targets. Interestingly, we show that by targeting Tnrc6a, miR-30 family miRNAs negatively regulate the miRNA pathway and modulate both the activity of muscle-specific miR-206 and the levels of protein synthesis. These findings indicate that the miR-30 family may be an interesting biomarker of perturbed muscle homeostasis and muscle disease.